PERBANDINGAN PENGUKURAN PDD DAN BEAM PROFILE ANTARA DETEKTOR IONISASI CHAMBER DAN GAFCHROMIC FILM PADA LAPANGAN 10 X 10 CM2 - Hamzah Fuadi; Heri Sutanto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
The Comparison of PDD and beam profile measurements between detectors Ionization Chamber and Gafchromic film on 10x10 cm2 field. has been done Measurements were made with the detector CC-13s with a volume of 0.13 cc as a reference detector. Measurements were performed using IBA RFA phantom dosimeter. while the film measurement using solid water phantom gafchromic done. Measurements were taken at a field size of 10x10 cm2 in plane 6 MV linac with energy. Profile measurements performed using the SAD technique, with a depth of 10 cm for 6 MV. While the PDD measurements using SSD technique. From the results of this study are expected to know the PDD curve Beam profile and optimal dose measurement accuracy can be achieved in clinical treatment. well as the advantages and disadvantages of each detector and can be taken into consideration in selecting the optimal dosimeter according to the function that will be used. Key words: Small field dosimetry, ionization chamber, gafchromic film